Expression of aquaporin-1 in the human peritoneum and the effect of peritoneal dialysis on its expression - 方炜 钱家麒 余志远 陈诗书 (Chinese medical journal, 2003)
Objective To investigate the expression of aquaporin-1 (AQP1) in the human peritoneum and to evaluate the effect of peritoneal dialysis (PD) on its expression.Methods Peritoneal biopsies were obtained from normal subjects (n = 10 ), uremic nondialysis patients (n = 12 ) at catheter insertion and PD patients (n = 10 ) at the time of catheter removal,reinsertion or renal transplantation. Western blot, immuno-histochemical staining and reverse transcript-polymerase chain reaction (RT-PCR) techniques were used to investigate AQP1 expression.Results All peritoneal samples expressed AQP1 at both mRNA and protein levels. Western blot revealed a major band at 28 kD as well as more diffuse bands between 35 and 50 kD. The 28 kD band represents the nonglycosylated form of the protein while the 35 -50 kD bands correspond to glycosylated AQPI. Immunohistochemical staining found the positive deposits were distributed in the mesothelial cells, endothelial cells of capillaries, venules and small veins, whereas no signal was detected in the arterioles. Semi-quantitative analysis showed that AQP1 expression was remarkably stable in all samples, whatever their origin ( P > 0.05). Concluslons Our findings suggested that AQP1 is the molecular counterpart of an ultra small pore during PD.Secondly,the peritoneal mesothelial cell might also be involved in peritoneal transcellular water transport.As regards whether or not the structural or distributional alterations of AQP1 in the peritoneum may be more obviously expressed during PD,further study is needed.